RETRACTED: Tobacco Smoking Affects the Salivary Gram-Positive Bacterial Population - Grine, Ghiles; Royer, Arthur; Terrer, Elodie; Diallo, Ousmane Oumou; Drancourt, Michel; Aboudharam, Gérard (Frontiers in Public Health, 2019)
The microbial communities of the oral fluid are in direct contact with tobacco smoke, which may thus affect these communities. Few culture-based studies have analyzed the effects of tobacco smoking on the oral fluid microbiota. Using bacterial culture we investigated whether tobacco smoking altered the microbial diversity of the oral fluid, focusing on aerobic and facultative anaerobic Gram-positive bacteria otherwise comprising of major pathogens. Among 90 oral fluid specimens collected in 19 tobacco-smokers and 71 controls, the diversity did not significantly differ with age and with sex. However, diversity was significantly lower in tobacco-smokers (nine different species) than in non-smokers (18 different species) with all the species cultured in tabocco-smokers being also cultured in non-smokers. We isolated the human pathogen Streptococcus australis for the first time from oral fluid. Tobacco smoking significantly alters the saliva Gram-positive bacterial microbiota, including pathogens with potential implication in the pathogenesis of tobacco-related diseases such as periodontitis and peri-implantitis.